The Impact of Professional Development Activities on ESL Teachers’ Growth: A Study Based on Government Universities - Silva, R.R.P.; Abeyweera, G.H.; Samarasinghe, A.G.S.M.; Herath, H.M.D.N.; Nayanahari, W.M.L.; Dissanayake, D.M.R.N. (University of Jaffna, 2025)
Teacher Professional Development (TPD) can be defined and measured in terms of skills, updated and upgraded knowledge, effective use of teaching strategies, teaching experience, lifelong learning, socio cultural understanding and overall growth of the ESL teacher. An ESL practitioner can gain professional development by engaging in both independent and sponsored teacher professional development activities such as; seminars, workshops, and programmes like TESOL, TEFL, and CELTA. The general aim of this study was to identify the impact of Teacher Professional Development activities on ESL teachers’ overall growth and development. The specific objectives were to identify the contribution of Independent and Sponsored Teacher Professional Development Activities to teacher agency, teacher efficacy, teacher quality, teacher professional capital, and teacher’s overall growth and as well as to explore the limitations of Teacher Professional Development activities. The research question was; how can ESL practitioners benefit from TPD activities? This study employs both qualitative and quantitative methods. The data were collected from 30 participants who were selected using a stratified random sampling method. A questionnaire was distributed among 30 ESL academic staff members of Sri Lankan government universities to identify the general aim of this research and interviews were conducted with the same set of participants from different age groups to explore the specific objectives. The primary data collected for the study were presented statistically and analyzed descriptively, mainly through theoretical frameworks such as; Piaget’s Constructivism, Vygotsky’s Socio-cultural Theory, Bandura’s Social Cognitive Theory, Becker’s Human Capital Theory, and Professional Capital Framework by Hargreaves and Fullan. The data presentation suggests that most ESL practitioners have benefited from both Independent and Sponsored TPD activities.The main positive impacts identified from the coded data were; promoting lifelong learning, upgrading and updating knowledge, building confidence, gaining practical exposure, incorporating technology, and promoting collaborative learning. In contrast, data also demonstrated some limitations in TPD activities such as; lack of motivation to conduct research, technological challenges for adult ESL learners, and generation gap between the educators and learners. Therefore, the outcome of the study reflects both positive and negative impacts of TPD activities and highlights the contribution of TPD activities to teacher agency, teacher efficacy, teacher quality, teacher professional capital, and teacher’s overall growth and development, with the aim of benefiting the academic careers of ESL practitioners.
Keywords: Teacher Professional Development (TPD) Activities; English as a Second Language (ESL); Teacher agency; Teacher efficacy; Teacher professional capital